2015
DOI: 10.1002/fsn3.212
|View full text |Cite
|
Sign up to set email alerts
|

A first study comparing preservation of a ready‐to‐eat soup under pressure (hyperbaric storage) at 25°C and 30°C with refrigeration

Abstract: Hyperbaric storage (HS), storage under pressure at 25°C and 30°C, of a ready‐to‐eat (RTE) soup was studied and compared with refrigeration. Soup was stored at different time (4 and 8 h), temperature (4°C, 25°C, and 30°C), and pressure (0.1, 100, and 150 MPa) conditions, to compare microbial loads and physicochemical parameters. HS resulted in similar (microbial growth inhibition) to better (microbial inactivation) results compared to refrigeration, leading to equal and lower microbial loads, respectively, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The unfortunate accident that occurred in 1968 with the research submarine Alvin was the starting point for HS since although sunk over 10 months at 1540 m (≈15 MPa) and 4 °C, some foods were found in consumable conditions when it was recovered . Since then, and mainly after 2012, several food products have been successfully preserved under pressure at controlled or variable RT, including fruit juices, ready‐to‐eat meals, sliced cooked ham, raw meat and raw fish …”
Section: Introductionmentioning
confidence: 99%
“…The unfortunate accident that occurred in 1968 with the research submarine Alvin was the starting point for HS since although sunk over 10 months at 1540 m (≈15 MPa) and 4 °C, some foods were found in consumable conditions when it was recovered . Since then, and mainly after 2012, several food products have been successfully preserved under pressure at controlled or variable RT, including fruit juices, ready‐to‐eat meals, sliced cooked ham, raw meat and raw fish …”
Section: Introductionmentioning
confidence: 99%
“…Kilinc [28] andÖztürk et al [29] observed that the value of pH fluctuated at different periods of storage time. Certainly, the pH depends on the type of soup and its composition [30,31]. In our case, the pH of both organic and nonorganic vegetable soups remained stable during the 96 h of storage time that might be due to the low production of organic acids in vegetable soup during the storage.…”
Section: Colour and Ph Of Soups During Storage Tablementioning
confidence: 54%
“…Moreover, the overall physicochemical analyses (e.g. pH, total soluble solids, cloudiness, browning degree, colour, enzymes, among others) in these studies allowed the conclusions that generally, there were no considerable differences between samples stored under pressure and RF, the main exceptions not usually being relevant for consumers (Moreira et al , ; Pinto et al , ; Fidalgo et al , ). Although sensorial analyses are still lacking regarding food products stored by HS, a study performed by Otero et al () on hake loins concluded that even though perceptible, the differences between samples previous to any storage time and stored under pressure seem not to be large since only moderate evidence of apparent differences was found (mainly in texture characteristics).…”
Section: Introductionmentioning
confidence: 89%